Liquidity Problems and Early Payment Default among Subprime Mortgages - Anderson, Nathan B.; Dokko, Jane K. (The Review of Economics and Statistics, 2016)
We compare the twelve-month default probability among subprime borrowers differing only in the number of months before their first lump-sum property tax payment, after which time they may be exposed to reduced liquidity. We show that borrowers with an earlier property tax bill—within three months of origination—have 2% to 6% higher first-year default rates than borrowers facing their first property tax bill ten to twelve months after origination. Lump-sum property tax payments appear to produce a persistent state of low liquidity, the length of which raises the likelihood of default. These results are about one-third the effect size of a transition from 10% positive to 20% negative equity found in the literature. This paper provides causal evidence that liquidity constraints are important predictors of mortgage default.